PENGEMBANGAN MEDIA VIDEO PEMBELAJARAN BERBASIS POWTOON PADA PEMBELAJARAN PENDIDIKAN PANCASILA DI KELAS IV SEKOLAH DASAR - Pransiska; Erita, Yeni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the minimal use of technology for the renewal of learning tools in schools optimally. Students feel conventional media is less helpful and causes boredom, while Learning Video Media is considered more interesting, relevant, and supports the effective learning process. This situation causes the learning process to be less varied and less interesting, thus making students tend to get bored during the learning process. The purpose of this study is to develop Powtoon-based learning video media in Pancasila Education Learning in grade IV elementary schools that are valid, practical, and effective. This type of research is a research with the development of the ADDIE model which consists of 5 stages, namely Analysis, design, development, implementation, and evaluation. The data for this study uses a validation sheet and a media expert questionnaire. The response questionnaire consists of teacher and student response questionnaires. The trial subjects in the study were 27 students in grade IV of SDN 03 Pakan Labuah and the research subjects consisted of 24 students in grade IV of SDN 01 Ladang Cakiah and the research subjects consisted of 29 students in grade IV of SDN 08 Kubu Tanjung. The results of the study showed that the Powtoon-based learning video media developed obtained language validity of 96.42% (very valid), material validity of 79.16% (valid), and media validity of 92.10% (very valid). The practicality test of the teacher response questionnaire obtained 95%, -97.5% and 97.59%, 95.72%, 92.32% of the student response questionnaire. The effectiveness test reached 88%, -90.83%, (very valid). The study concluded that the Powtoon-based learning video media developed for Pancasila Education in fourth-grade elementary schools was valid, practical, and effective for use in the learning process. Keywords: Learning Media, Powtoon, Pancasila Education, ADDIE